2017
DOI: 10.22256/pubvet.v12n1a16.1-4
|View full text |Cite
|
Sign up to set email alerts
|

Sertolioma em um canino associado à criptorquidia

Abstract: The sertolioma is one of the tumors that most affect older dogs, more incidents in criptorquidas animals. Usually these tumors are extremely expansive and can compress and destroy adjacent tissues. For their identification is necessary to carry out histopathological examination. This study aimed to report the occurrence of gonadopatia right criptorquidica, accompanied by neoplastic process associated in a dog of 10 years old. After orchiectomy the testes were sent to the Animal Pathology Laboratory of the Fede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
2
0
3
Order By: Relevance
“…Coinciding with the information that the occurrence of testicular tumors in cryptorchid patients is commonly reported (CIAPUTA et al, 2012;HOLST et al, 2015;ARGENTA et al, 2017;FARIA et al, 2017), being the most common sertolioma (NODTVEDT et al, 2011;CIAPUTA et al, 2012;HOLST et al, 2015;ARGENTA., 2017;FARIA et al, 2017), it was observed in this report a unilateral cryptorchid canine that developed the neoplasm.…”
Section: Discussion and Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Coinciding with the information that the occurrence of testicular tumors in cryptorchid patients is commonly reported (CIAPUTA et al, 2012;HOLST et al, 2015;ARGENTA et al, 2017;FARIA et al, 2017), being the most common sertolioma (NODTVEDT et al, 2011;CIAPUTA et al, 2012;HOLST et al, 2015;ARGENTA., 2017;FARIA et al, 2017), it was observed in this report a unilateral cryptorchid canine that developed the neoplasm.…”
Section: Discussion and Resultsmentioning
confidence: 81%
“…Sertolioma, one of the most common testicular neoplasms, is frequent in elderly, uncastrated and cryptorchid dogs, a factor that predisposes the development of this tumor, since it is commonly manifested unilaterally (MEUTEN, 2002;FARIA et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A ocorrência de tumores testiculares em pacientes criptorquidas é comumente relatada (CIAPUTA et al, 2012;HOLST & DREIMANIS, 2015;ARGENTA et al, 2017;FARIA et al, 2017), sendo o sertolioma o de maior ocorrência (NODTVEDT et al, 2011;CIAPUTA et al, 2012;HOLST & DREIMANIS, 2015;ARGENTA, 2017;FARIA et al, 2017), assim como o observado nesse relato de caso, onde o canino era criptorquida unilateral e desenvolveu sertolioma.…”
Section: Discussionunclassified
“…Existem três tipos de tumores testiculares frequentemente relatados, que se originam em células de leidig, sertoli e/ou seminoma, são geralmente benignas, e dificilmente fazem metástase (NODTVEDT et al, 2011;ARGENTA., 2017). O sertolioma é uma das neoplasias testiculares mais comuns, e a sua ocorrência é mais frequente em caninos, idosos e que não sejam castrados, e, ainda, em animais que os testículos não desceram para o saco escrotal, ou seja, aqueles que são criptorquidas (NODTVEDT et al, 2011;CIAPUTA et al, 2012;HOLST & DREIMANIS, 2015;ARGENTA., 2017;FARIA et al, 2017). Sendo esse um dos fatores que contribuem para o desenvolvimento desse tipo de tumor, manifestado de forma unilateral mais comumente em sertoliomas (MEUTEN, 2002;FARIA et al, 2017).…”
Section: Introductionunclassified

Sertolioma em um canino: relato de caso

Pinto de Oliveira Lima,
Da Fontoura Moura,
Moukaddem de Souza
et al. 2023
PRW
“…Os sertoliomas, seminomas e leydigocitomas costumam apresentar um comportamento benigno (FARIA et al, 2018). A taxa de malignidade pode variar de 10 a 20% nas neoplasias das células de Sertoli, 5 a 10% nos seminomas e rareando nas neoplasias das células intersticiais (ALBERS et al, 2009).…”
Section: Introductionunclassified